Logística internacional de la exportación de arequipe a México (2019)
In this work the international logistics for the export of Arequipe from Colombia to Mexico was made, using the Total Quality Management (TQM) model as the basis for the realization of the work. The TQM model was chosen since it always focuses on the client, since if the client finds total satisfaction in the delivery of the merchandise it means that the processes are being carried out in the best way.